Imagining autism : fiction and stereotypes on the spectrum - Loftis, Sonya Freeman, 1983- (Bloomington : Indiana University Press, 2015)
"A disorder that is only just beginning to find a place in disability studies and activism, autism remains in large part a mystery, giving rise to both fear and fascination. Sonya Loftis's groundbreaking study turns to literary representations of autism or autistic behavior to discover what impact they have had on cultural stereotypes, autistic culture, and the identity politics of autism. Imagining Autism looks at literary characters (and an author or two) widely understood as autistic, ranging from Conan Doyle's Sherlock Holmes, Shaw's St. Joan, Steinbeck's Lennie Small, and Harper Lee's Boo Radley to Mark Haddon's boy detective Christopher Boone and Steig Larsson's Lisbeth Salander. The silent figure trapped inside himself, the savant made famous by his other-worldly intellect, the brilliant detective linked to the criminal mastermind by their common neurology--in these works characters on the spectrum become protean symbols, stand-ins for the chaotic forces of inspiration, contagion, and disorder. These powerful fictional depictions, Loftis argues, are also part of the imagined lives of the autistic, sometimes for good, sometimes threatening to undermine self-identity and the activism of the autistic community"--
The autistic detective: Sherlock Holmes and his legacy -- The autistic savant: Pygmalion, Saint Joan, and the neurodiversity movement -- The autistic victim: Of mice and men and Flowers for Algernon -- The autistic gothic: To kill a mockingbird, The glass menagerie, and The sound and the fury -- The autistic child narrator: Extremely loud and incredibly close and The curious incident of the dog in the night-time -- The autistic label: diagnosing (and undiagnosing) The girl with the dragon tattoo -- Afterword.
Includes bibliographical references (pages 157-187) and index.
Keywords: Autistic people in literature; Identity (Psychology) in literature; English fiction -- History and criticism; American fiction -- History and criticism; American drama -- 20th century -- History and criticism; English drama -- 20th century -- History and criticism; Stereotypes (Social psychology)